2020
DOI: 10.1371/journal.pone.0242279
|View full text |Cite
|
Sign up to set email alerts
|

Heat and dehydration induced oxidative damage and antioxidant defenses following incubator heat stress and a simulated heat wave in wild caught four-striped field mice Rhabdomys dilectus

Abstract: Heat waves are known for their disastrous mass die-off effects due to dehydration and cell damage, but little is known about the non-lethal consequences of surviving severe heat exposure. Severe heat exposure can cause oxidative stress which can have negative consequences on animal cognition, reproduction and life expectancy. We investigated the current oxidative stress experienced by a mesic mouse species, the four striped field mouse, Rhabdomys dilectus through a heat wave simulation with ad lib water and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 113 publications
0
18
0
2
Order By: Relevance
“…In support of this mechanism, a recent study revealed that baseline corticosterone levels were higher in water-deprived house sparrows (Brischoux et al, 2020), and glucocorticoid has been shown to disturb cellular oxidative homeostasis (Costantini et al, 2011;Queisser et al, 2011). Furthermore, recent evidence indicates that dehydration induced by high environmental temperatures influences cellular metabolism in mammals, ultimately yielding an elevated antioxidant response and/or oxidative damage (Jacobs et al, 2020). It remains unknown whether hydration state and changes in osmotic conditions may cause oxidative damage in birds.…”
Section: Introductionmentioning
confidence: 99%
“…In support of this mechanism, a recent study revealed that baseline corticosterone levels were higher in water-deprived house sparrows (Brischoux et al, 2020), and glucocorticoid has been shown to disturb cellular oxidative homeostasis (Costantini et al, 2011;Queisser et al, 2011). Furthermore, recent evidence indicates that dehydration induced by high environmental temperatures influences cellular metabolism in mammals, ultimately yielding an elevated antioxidant response and/or oxidative damage (Jacobs et al, 2020). It remains unknown whether hydration state and changes in osmotic conditions may cause oxidative damage in birds.…”
Section: Introductionmentioning
confidence: 99%
“…They found that exercise affects immune system and that the number of leukocytes, neutrophils, lymphocytes, and natural killer cells were higher as a result of exercise. It has been also demonstrated that dehydration is closely related with oxidative stress [8]. Evidently oxidative damage leads to disruption of tissue integrity and to the increase of tissue permeability.…”
Section: Introductionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) may be of profound biological importance as it has been demonstrated to mediate these high investment processes (Alonso-Alvarez et al, 2004;Dowling and Simmons, 2009;Viblanc et al, 2018;Costantini, 2019). Aerobic organisms constantly produce ROS from metabolism, where excessive ROS is reduced through antioxidants, whereby the body is trying to maintain redox balance and reduce ROS to below harmful levels (Birben et al, 2012;Jacobs et al, 2020Jacobs et al, , 2021b. When ROS levels are elevated above normal levels, a state of oxidative stress (OS), can overwhelm antioxidant defences resulting in damaging proteins, lipids, and DNA (Sies, 1991;Finkel and Holbrook, 2000;Costantini, 2008), all of which can compromise both reproduction and survival.…”
Section: Introductionmentioning
confidence: 99%